Phương pháp ép tích giải phương trình vô tỷ

  • Số trang: 44 |
  • Loại file: PDF |
  • Lượt xem: 3923 |
  • Lượt tải: 8
dangvantuan

Đã đăng 43037 tài liệu

Mô tả:

“𝑺𝒉𝒊𝒇𝒕” “𝑺𝑶𝑳𝑽𝑬” 1 “𝑺𝒐𝒍𝒗𝒆 𝒇𝒐𝒓 𝑿” √𝒙 + 𝟐 = 𝟐𝒙𝟐 + 𝒙 − 𝟖 “𝑺𝒉𝒊𝒇𝒕” “𝑺𝑶𝑳𝑽𝑬” 2 𝑻𝑨𝑩𝑳𝑬 𝒈(𝒙) 𝑨𝟐 + 𝑨𝑿 “=” “𝑺𝒕𝒂𝒓𝒕? ” “ − 𝟏𝟒” “=” “𝑬𝒏𝒅? ” “𝟏𝟒” “=” “𝑺𝒕𝒆𝒑? ” “𝟏” “=” 𝒇(𝒙) 3 𝑨𝟐 𝒙𝟑 + 𝒙𝟐 = (𝒙𝟐 + 𝟏)√𝒙 + 𝟏 + 𝟏 𝒙 = 𝟏. 𝟔𝟏𝟖 … … 4 𝒙𝟐 − 𝒙 − 𝟏 𝒇(𝒙) = 𝑨𝟐 + 𝑨𝑿 5 𝑨𝟐 − 𝑨 = 𝟏  𝑨𝟐 − 𝑨 − 𝟏 = 𝟎 𝒇(−𝟏) = 𝟏 𝒙𝟐 − 𝒙 − 𝟏 𝒙 √ √ 𝒂 = (√ ) 𝒂𝒙 + 𝒃 = √ ′ 𝒂 𝒃 √𝒙 + 𝟐 = 𝟐𝒙𝟐 + 𝒙 − 𝟖 𝒙=𝟐 √𝒙 + 𝟐 − 𝟐 6 𝟐( 𝒙𝟐 − 𝟗𝒙 + 𝟏𝟎)√𝒙 − 𝟏 + 𝒙𝟑 − 𝟖𝒙𝟐 + 𝟔𝒙 + 𝟖𝟓 = 𝟎 𝒙=𝟓 𝒂 = (√𝒙 − 𝟏) 𝒂= ′ 𝒙=𝟓 𝟏 𝟒 𝟏 𝟓. + 𝒃 = 𝟐 𝟒 𝒃= 𝟑 𝟒 𝒙+𝟑 √𝒙 − 𝟏 − ( 𝟒 ) 𝒂𝒙 + 𝒃 = √ 𝒂, 𝒃 𝟑√𝒙 + 𝟏 = 𝟑𝒙𝟐 − 𝟖𝒙 + 𝟑 𝒙=𝟎 𝒙=𝟑 𝒃=𝟏 𝟎𝒂 + 𝒃 = 𝟏 𝟏 { { 𝒂= 𝟑𝒂 + 𝒃 = 𝟐 𝟑 𝒙+𝟑 √𝒙 + 𝟏 − ( 𝟑 ) 7 𝒂𝒙 + 𝒃 = √ 𝒂, 𝒃 √ √ 𝑨𝒂 + 𝒃 = 𝑪 { 𝑩𝒂 + 𝒃 = 𝑫 √ + 𝑨𝒙 √ (𝒙 + 𝟒)√𝒙 + 𝟐 = 𝒙𝟑 − 𝒙𝟐 − 𝒙 − 𝟓 8 𝑿 = 𝟑. 𝟑 … .. √𝒙 + 𝟐 − (𝒙 − 𝟏) 9 𝒂𝟐 − 𝒃𝟐 = (𝒂 + 𝒃)(𝒂 − 𝒃) 𝒂𝟑 − 𝒃𝟑 = (𝒂 − 𝒃)(𝒂𝟐 + 𝒂𝒃 + 𝒃𝟐 ) 𝒂𝟑 + 𝒃𝟑 = (𝒂 + 𝒃)(𝒂𝟐 − 𝒂𝒃 + 𝒃𝟐 ) 𝒂𝟒 − 𝒃𝟒 = (𝒂 + 𝒃)(𝒂 − 𝒃)(𝒂𝟐 + 𝒃𝟐 ) (𝟕𝒙 − 𝟗)√𝟕𝒙 − 𝟏𝟎 = 𝟐𝒙𝟑 − 𝟕𝒙𝟐 + 𝟏𝟏𝒙 {𝟐; 𝟓} { 𝟐𝒂 + 𝒃 = 𝟐 𝒂=𝟏 { 𝟓𝒂 + 𝒃 = 𝟓 𝒃=𝟎 √𝟕𝒙 − 𝟏𝟎 − 𝒙 (√𝟕𝒙 − 𝟏𝟎 − 𝒙)(√𝟕𝒙 − 𝟏𝟎 − 𝒙) = −(𝒙𝟐 − 𝟕𝒙 + 𝟏𝟎) 10 𝒙≥ 𝟏𝟎 𝟕 𝟐𝒙(𝒙𝟐 − 𝟕𝒙 + 𝟏𝟎) + (𝟕𝒙 − 𝟗)(𝒙 − √𝟕𝒙 − 𝟏𝟎) = 𝟎  𝟐𝒙(𝒙 − √𝟕𝒙 − 𝟏𝟎)(𝒙 + √𝟕𝒙 − 𝟏𝟎) + (𝟕𝒙 − 𝟗)(𝒙 − √𝟕𝒙 − 𝟏𝟎) = 𝟎  (𝒙 − √𝟕𝒙 − 𝟏𝟎)(𝟐𝒙𝟐 + 𝟕𝒙 − 𝟗 + 𝟐𝒙√𝟕𝒙 − 𝟏𝟎) = 𝟎 𝟐𝒙𝟐 + 𝟕𝒙 − 𝟗 + 𝟐𝒙√𝟕𝒙 − 𝟏𝟎 > 𝟎∀𝒙 ≥ 𝟏𝟎 𝟕  √𝟕𝒙 − 𝟏𝟎 = 𝒙  𝒙𝟐 − 𝟕𝒙 + 𝟏𝟎 = 𝟎  𝒙 = 𝟐 𝒙 = 𝟓 𝑺 = {𝟐; 𝟓} (𝒙 + 𝟒)√𝒙 + 𝟐 = 𝒙𝟑 − 𝒙𝟐 − 𝒙 − 𝟓 𝑿 = 𝟑. 𝟑 … .. √𝒙 + 𝟐 − (𝒙 − 𝟏) (√𝒙 + 𝟐 − (𝒙 − 𝟏)) (√𝒙 + 𝟐 + (𝒙 − 𝟏)) = −(𝒙𝟐 − 𝟑𝒙 − 𝟏) 11 𝒙 ≥ −𝟐 𝒙𝟑 − 𝟐𝒙𝟐 − 𝟒𝒙 − 𝟏 + (𝒙 + 𝟒)(𝒙 − 𝟏 − √𝒙 + 𝟐) = 𝟎 (𝒙 + 𝟏)(𝒙𝟐 − 𝟑𝒙 − 𝟏) + (𝒙 + 𝟒)(𝒙 − 𝟏 − √𝒙 + 𝟐) = 𝟎 (𝒙 + 𝟏)(𝒙 − 𝟏 − √𝒙 + 𝟐)(𝒙 − 𝟏 + √𝒙 + 𝟐) + (𝒙 + 𝟒)(𝒙 − 𝟏 − √𝒙 + 𝟐) = 𝟎  (𝒙 − 𝟏 − √𝒙 + 𝟐) ((𝒙 + 𝟏)√𝒙 + 𝟐 + 𝒙𝟐 + 𝒙 + 𝟑) = 𝟎 (𝒙 + 𝟏)√𝒙 + 𝟐 + 𝒙𝟐 + 𝒙 + 𝟑 > 𝟎 ∀𝒙 ≥ −𝟐 𝟑+√𝟏𝟑 𝒙≥𝟏  𝒙 − 𝟏 = √𝒙 + 𝟐 { 𝟐 𝒙 = 𝟐 𝒙 − 𝟑𝒙 − 𝟏 = 𝟎 𝟑+√𝟏𝟑 𝑺={ 𝟐 } 𝟏𝟎𝒙𝟐 + 𝟑𝒙 − 𝟔 − 𝟐(𝟑𝒙 + 𝟏)√𝟐𝒙𝟐 − 𝟏 = 𝟎 12 𝑿 = 𝟏. 𝟑𝟗 … .. 𝑿 = −𝟎. 𝟖𝟐 … .. 𝑿 = 𝟎. 𝟕𝟐 … .. 𝑨 + 𝑩 = 𝒍ẻ 𝟖 { 𝑨𝑩 = − 𝟕 𝟕(𝑨 + 𝑩) = 𝟒 𝟏 𝒂= 𝟐 { 𝒃=𝟏 𝑿 = 𝟏. 𝟑𝟗 … .. √𝟐𝒙𝟐 − 𝟏 𝑿 = −𝟎. 𝟖𝟐 …. 𝑿 = 𝟎. 𝟕𝟐 … .. 𝟐√𝟐𝒙𝟐 − 𝟏 − (𝒙 + 𝟐) 𝟐 𝟐√𝟐𝒙𝟐 − 𝟏 − (𝒙 + 𝟐) 𝟐√𝟐𝒙𝟐 − 𝟏 − (𝟐𝒙 − 𝟏) (𝟐√𝟐𝒙𝟐 − 𝟏 − (𝒙 + 𝟐)) (𝟐√𝟐𝒙𝟐 − 𝟏 + (𝒙 + 𝟐)) = 𝟕𝒙𝟐 − 𝟒𝒙 − 𝟖 13 𝒙 ∈ (−∞; − √𝟐 ] 𝟐 ∪[ √𝟐 ; +∞) 𝟐 𝟕𝒙𝟐 − 𝟒𝒙 − 𝟖 + (𝟑𝒙 + 𝟏) (𝒙 + 𝟐 − 𝟐√𝟐𝒙𝟐 − 𝟏) = 𝟎  (𝟑𝒙 + 𝟏)(𝒙 + 𝟐 − 𝟐√𝟐𝒙𝟐 − 𝟏) − (𝒙 + 𝟐 − 𝟐√𝟐𝒙𝟐 − 𝟏)(𝒙 + 𝟐 + 𝟐√𝟐𝒙𝟐 − 𝟏) = 𝟎  (𝒙 + 𝟐 − 𝟐√𝟐𝒙𝟐 − 𝟏) ((𝟑𝒙 + 𝟏) − (𝒙 + 𝟐 + 𝟐√𝟐𝒙𝟐 − 𝟏)) = 𝟎  (𝒙 + 𝟐 − 𝟐√𝟐𝒙𝟐 − 𝟏)(𝟐𝒙 − 𝟏 − 𝟐√𝟐𝒙𝟐 − 𝟏) = 𝟎  𝟐√𝟐𝒙𝟐 − 𝟏 = 𝒙 + 𝟐 𝟐𝒙 − 𝟏 = 𝟐√𝟐𝒙𝟐 − 𝟏  𝟕𝒙𝟐 − 𝟒𝒙 − 𝟖 = 𝟎 𝒙 = 𝟐±𝟐√𝟏𝟓 𝟕 𝒙= 𝟒𝒙𝟐 + 𝟒𝒙 − 𝟓 = 𝟎 −𝟏±√𝟔 𝑺= 𝟐 𝟐 ± 𝟐√𝟏𝟓 −𝟏 + √𝟔 { ; } 𝟕 𝟐 𝟐𝒙𝟐 + 𝟓𝒙 − 𝟏 = 𝟕√𝒙𝟑 − 𝟏 14 𝑿 = 𝟔. 𝟒𝟒𝟗 … .. { 𝑨𝑩 = 𝟏𝟎 𝑨+𝑩=𝟖 𝑿 = 𝟏. 𝟓𝟓 … 𝒙𝟐 − 𝟖𝒙 + 𝟏𝟎 = 𝟎 𝑨𝒂 + 𝒃 = 𝑪 𝒂=𝟑 { { 𝑩𝒂 + 𝒃 = 𝑫 𝒃 = −𝟑  √𝒙𝟑 − 𝟏 − (𝟑𝒙 − 𝟑) (√𝒙𝟑 − 𝟏 − (𝟑𝒙 − 𝟑)) (√𝒙𝟑 − 𝟏 + (𝟑𝒙 − 𝟑)) = 𝒙𝟑 − 𝟗𝒙𝟐 + 𝟏𝟖𝒙 − 𝟏𝟎 = (𝒙 − 𝟏)(𝒙𝟐 − 𝟖𝒙 + 𝟏𝟎) 𝒙𝟑 − 𝟗𝒙𝟐 + 𝟏𝟖𝒙 − 𝟏𝟎 15 𝒙𝟑 − 𝟏 ≥ 𝟎 𝒙 ≥ 𝟏 𝟐(𝒙𝟐 − 𝟖𝒙 + 𝟏𝟎) − 𝟕 (√𝒙𝟑 − 𝟏 − (𝟑𝒙 − 𝟑)) = 𝟎  𝟐(𝒙𝟐 − 𝟖𝒙 + 𝟏𝟎)(𝒙 − 𝟏) − 𝟕(𝒙 − 𝟏) (√𝒙𝟑 − 𝟏 − (𝟑𝒙 − 𝟑)) = 𝟎  𝟐 (√𝒙𝟑 − 𝟏 − (𝟑𝒙 − 𝟑)) (√𝒙𝟑 − 𝟏 + (𝟑𝒙 − 𝟑)) − 𝟕(𝒙 − 𝟏) (√𝒙𝟑 − 𝟏 − (𝟑𝒙 − 𝟑)) = 𝟎  (√𝒙𝟑 − 𝟏 − (𝟑𝒙 − 𝟑)) (𝟐√𝒙𝟑 − 𝟏 − 𝒙 + 𝟏) = 𝟎  √𝒙𝟑 − 𝟏 = (𝟑𝒙 − 𝟑) 𝟐√𝒙𝟑 − 𝟏 = 𝟏 − 𝒙  (𝒙 − 𝟏)(𝒙𝟐 − 𝟖𝒙 + 𝟏𝟎) = 𝟎 𝒙=𝟏 (𝒙 − 𝟏)(𝟒𝒙𝟐 + 𝟓𝒙 + 𝟓) = 𝟎 𝒙 = 𝟒 ± √𝟔 𝑺 = {𝟒 ± √𝟔} 16 (𝟒𝐱 𝟐 − 𝐱 − 𝟕)√𝐱 + 𝟐 = 𝟏𝟎 + 𝟒𝐱 − 𝟖𝐱 𝟐 𝐱 𝟑 − 𝟐𝐱 𝟐 + 𝟑𝐱 + 𝟑√𝟏𝟎 − 𝐱 𝟐 = 𝟏𝟏 𝟏𝟓𝒙𝟐 + 𝟏𝟐𝒙 + 𝟏𝟐 = 𝟏𝟎(𝟐𝒙 + 𝟏)√𝒙𝟐 + 𝟑 𝐱 𝟐 + 𝟓𝐱 = 𝟒(𝟏 + √𝐱 𝟑 + 𝟐𝐱 𝟐 − 𝟒𝐱) 𝟏 + 𝟑𝐱 = (𝐱 − 𝐱 𝟐 )(𝟓 + √𝟏𝟓 + 𝟔𝐱 − 𝟗𝐱 𝟐 ) 𝒙𝟑 + √𝒙𝟑 = (𝒙 + 𝟒)(𝒙 + 𝟓) (𝟐𝒙 + 𝟐)√𝒙𝟐 + 𝒙 + 𝟐 = 𝒙𝟐 + 𝟓𝒙 + 𝟐 𝒙𝟐 + 𝟔𝒙 + 𝟏 = (𝟐𝒙 + 𝟏)√𝒙𝟐 + 𝟐𝒙 + 𝟑 𝟖𝒙𝟐 + 𝟑𝒙 + (𝟒𝒙𝟐 + 𝒙 − 𝟐)√𝒙 + 𝟒 = 𝟒 𝟒𝒙𝟐 − 𝟑𝒙 = (𝒙 + 𝟐)√𝟐𝒙𝟐 + 𝟐𝒙 − 𝟏 𝒙𝟐 +𝟐𝒙−𝟖 𝒙𝟐 −𝟐𝒙+𝟑 = (𝒙 + 𝟏)(√𝒙 + 𝟐 − 𝟐) (𝟓𝐱 − 𝟏𝟔)√𝐱 + 𝟏 = √𝐱 𝟐 − 𝐱 − 𝟐𝟎(𝟓 + √𝟓𝐱 + 𝟗) (𝟔𝒙𝟐 + 𝟏𝟐𝒙 − 𝟔)√𝟐𝒙 − 𝟏 = 𝒙𝟑 + 𝟐𝟐𝒙𝟐 − 𝟏𝟏𝒙 𝟔𝒙𝟑 + 𝟏𝟓𝒙𝟐 + 𝒙 + 𝟏 = (𝟑𝒙𝟐 + 𝟗𝒙 + 𝟏)√𝒙𝟐 − 𝒙 + 𝟏 17 18 (𝟔𝒙𝟐 + 𝟏𝟐𝒙 − 𝟔)√𝟐𝒙 − 𝟏 = 𝒙𝟑 + 𝟐𝟐𝒙𝟐 − 𝟏𝟏𝒙 (𝟏) 𝒙≥ 𝟏 𝟐 −𝟐𝒙𝟑 + 𝟏𝟔𝒙𝟐 − 𝟖𝒙 + (𝟑𝒙𝟐 + 𝟔𝒙 − 𝟑)(𝒙 − 𝟐√𝟐𝒙 − 𝟏) = 𝟎  (𝒙 − 𝟐√𝟐𝒙 − 𝟏)(𝒙𝟐 + 𝟔𝒙 − 𝟑 − 𝟒𝒙√𝟐𝒙 − 𝟏) = 𝟎  (𝒙 − 𝟐√𝟐𝒙 − 𝟏)[−𝟑(𝒙𝟐 − 𝟐𝒙 + 𝟏) + 𝟒𝒙(𝒙 − √𝟐𝒙 − 𝟏)] = 𝟎  (𝒙 − 𝟐√𝟐𝒙 − 𝟏)(𝟏 − √𝟐𝒙 − 𝟏)(𝒙 − 𝟑√𝟐𝒙 − 𝟏) = 𝟎 𝟔𝒙𝟑 + 𝟏𝟓𝒙𝟐 + 𝒙 + 𝟏 = (𝟑𝒙𝟐 + 𝟗𝒙 + 𝟏)√𝒙𝟐 − 𝒙 + 𝟏(𝟐)  𝟑(𝟒𝒙𝟑 + 𝟏𝟑𝒙𝟐 + 𝟕𝒙 + 𝟏) − (𝟑𝒙𝟐 + 𝟗𝒙 + 𝟏)(√𝒙𝟐 − 𝒙 + 𝟏 + 𝟐𝒙 + 𝟐) = 𝟎 19
- Xem thêm -